A randomized study of solriamfetol for excessive sleepiness in narcolepsy. Issue 3 (28th February 2019) - Thorpy, Michael J.; Shapiro, Colin; Mayer, Geert; Corser, Bruce C.; Emsellem, Helene; Plazzi, Giuseppe; Chen, Dan; Carter, Lawrence P.; Wang, Hao; Lu, Yuan; Black, Jed; Dauvilliers, Yves
Abstract : Objective: Solriamfetol (JZP‐110) is a selective dopamine and norepinephrine reuptake inhibitor with wake‐promoting effects. This phase 3 study (NCT02348593) evaluated the safety and efficacy of solriamfetol in narcolepsy. Methods: Patients with narcolepsy with mean sleep latency <25 minutes on the Maintenance of Wakefulness Test (MWT), Epworth Sleepiness Scale (ESS) score ≥10, and usual nightly sleep ≥6 hours were randomized to solriamfetol 75, 150, or 300 mg, or placebo for 12 weeks. Coprimary endpoints were change from baseline to week 12 in MWT and ESS. Improvement on the Patient Global Impression of Change (PGI‐C) was the key secondary endpoint. Results: Safety and modified intention‐to‐treat populations included 236 and 231 patients, respectively. Solriamfetol 300 and 150 mg were positive on both coprimary endpoints. Least squares mean (standard error [SE]) changes from baseline were 12.3 (SE = 1.4) and 9.8 (SE = 1.3) minutes for solriamfetol 300 and 150 mg on the MWT, respectively, versus 2.1 (SE = 1.3) minutes for placebo, and −6.4 (SE = 0.7) for 300 mg and −5.4 (SE = 0.7) for 150 mg on the ESS versus −1.6 (SE = 0.7) for placebo (all p < 0.0001). At week 12, higher percentages of patients treated with solriamfetol 150 mg (78.2%) and 300 mg (84.7%) reported PGI‐C improvement relative to placebo (39.7%; both p < 0.0001). Adverse events ≥5% across all solriamfetol doses included headache (21.5%), nausea (10.7%), decreased appetite (10.7%), nasopharyngitis (9.0%), dry mouth (7.3%), and anxiety (5.1%). Interpretation: Solriamfetol has the potential to be an important therapeutic option for the treatment of impaired wakefulness and excessive sleepiness in patients with narcolepsy. ANN NEUROL 2019;85:359–370.